Influence of hydrothermal pretreatment on acidity and activity of H-GaAlMFI zeolite for the propane aromatization reaction - Choudhary, Tushar V.; Kinage, A.; Banerjee, S.; Choudhary, Vasant R. (Microporous and Mesoporous Materials, 2005)
The acidity and propane aromatization activity of H-GaAlMFI has been investigated subsequent to different hydrothermal (HT) pretreatments. Extensive degalliation of framework Ga occurred during the HT pretreatments; the framework Si/Ga ratio nearly doubled when the steam concentration was increased from 0% to 80%. The extent of degalliation and corresponding loss of strong zeolitic acidity (measured in terms of pyridine chemisorbed at 400 degrees C) was particularly severe at high (> 500 degrees C) temperatures and steam concentrations (> 40 mol%). Framework Al in the GaAlMFI zeolite was found to be very stable; the FW Si/Al ratio did not change to any appreciable extent even after severe HT pretreatments. Each of the HT pretreatment parameters (concentration of steam: 0-80%, HT temperature: 400-600 degrees C and length of HT pretreatment: 0-6 h) showed a profound influence on the propane aromatization activity. The product selectivity was, however, only mildly affected by the HT pretreatments. The following factors were found to be important for high propane aromatization activity (a) strong zeolitic acidity and (b) optimal content/dispersion of the extra-framework Ga species which are formed in situ during the HT pretreatments. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: Acidity; aromatic distribution; Ga-based zeolites; hydrothermal treatment and steam; propane aromatization

Propane conversion to aromatics on highly active H-GaAlMFI: effect of thermal pretreatment - Choudhary, Tushar V.; Kinage, A.; Banerjee, S.; Choudhary, Vasant R. (Energy & Fuel, 2006)
The propane aromatization activity over H-GaAlMFI has been investigated after different thermal pretreatments ( calcination temperature range: 500- 800 degrees C) at a reaction temperature of 500 degrees C and in the space velocity range of 1500-12000 cm(3)/g/h. The calcination temperature had a strong influence on the strong acidity of the zeolite, propane conversion, and aromatic distribution. The decrease in acidity with increased thermal treatment severity correlated well with the decrease in the framework Ga. There was a considerable decrease in propane aromatization activity at calcination temperatures above 600 degrees C. The effect of calcination temperature on the propane aromatization activity can be explained in terms of change in the strong acidity of the zeolite and the extraframework Ga content. The selectivity for aromatics was found to decrease with increasing thermal pretreatment severity, while that for methane, ethane, and propylene was found to increase. The aromatic distribution was also influenced by the thermal pretreatment; the selectivity for benzene increased with increasing pretreatment temperature, while the selectivity for toluene, C-8 aromatics, and C9+ aromatics decreased.